Haloperidol-Induced Extrapyramidal Symptoms in a Young Male with Alcohol Dependence Syndrome and Emotionally Unstable Personality Disorder - K, Arunkumar; Gurumoorthy, Haripriya (Indian Journal of Pharmacy Practice)
Aim/Background: To report a case of haloperidol-induced Extrapyramidal Symptoms (EPSEs) in a young male with alcohol dependence syndrome and emotionally unstable personality disorder. Materials and Methods: A 27-year-old male with chronic alcohol use, seizure disorder, and personality disorder was initiated on haloperidol during complicated alcohol withdrawal. ADRs were assessed using WHO-UMC and Naranjo scales. Results: The patient developed tremors within 24 hr despite prophylactic trihexyphenidyl. Haloperidol was discontinued and replaced with quetiapine, leading to complete symptom resolution. Causality assessment indicated a probable reaction. Conclusion: Even low-dose haloperidol can induce EPSEs in vulnerable populations. Prompt identification, drug withdrawal, and substitution with safer antipsychotics are essential.
Keywords: Haloperidol; Extrapyramidal Symptoms; Alcohol Dependence; Diazepam; Naranjo; Scale; WHO-UMC; Adverse Drug Reaction